Pengembangan Modul Ajar PAI Kelas VIII Berbasis Teka Teki Silang di SMPN 5 Bukittinggi - Halimah, Lusiana; S, Supriadi; J, Junaidi; Arsya, Fajriyani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research was motivated because the teaching tools used at SMPN 5 Bukittinggi in the form of teaching modules, in the knowledge assessment component in the form of multiple choice questions and descriptions, found several weaknesses when applied, including: student learning outcomes when the application of assessments in PAI subjects is low, has not reaced KKTP, besides that the knowledge assessment applied by the teacher is less varied and the knowledge assessment applied is less interesting foe students in learning, tends to be monotonous and boring.Therefore, it is necessary to design a Crossword-based PAI Teaching Module that is valid, practical and effective. This research is a development research with the ADDIE model, consisting of five stages of development, namely analysis, design, development, implementation and evaluation. The instruments used are validity, practicality, and effectiveness sheets in the form of questionnaires. The results showed that the teaching module was valid according to the assessment of 3 experts with an average score of 0.851; (2) the teaching module was very practical according to the assessment of 2 practitioners with a practicality percentage of 90.17%; (3) the teaching module was very effective with a percentage of effectiveness of 89.73%.